Liver in guinea pig: Scanning and transmission electron microscopic studies. Issue 10 (4th July 2022) - Rajathi, Shunmugam; Ramesh, Geetha; Kannan, Thandavan Arthanari; Dharani, Palanisamy; Gnanadevi, Ravignanam
Abstract: The liver performs many functions, which support metabolism, immunity, digestion, detoxification, vitamin storage, and so on. The liver is the storage organ for fat‐soluble vitamins, iron and copper. Six adult healthy guinea pigs of 16–32 weeks of age (Irrespective of sex) were procured from the Department of Laboratory Animal Medicine, TANUVAS as per ethical committee approval. Animals were dissected as per CPCSEA norms and liver pieces were utilized for scanning electron microscopy (SEM) and transmission electron microscopy (TEM) study. The study was performed to document the ultrastructural details of liver of guinea pigs by SEM and TEM. By SEM, the liver parenchyma appeared as lobular with anastomosed one cell thick hepatic cell plates, which appeared as continuous sheets with small to large holes representing sinusoids. The sinusoidal lumen was lined by two types of cells namely endothelial cells and Kupffer cells. Endothelial cells had numerous large and small cytoplasmic fenestrations. Presence of Kupffer cells along with Ito cells were observed in the sinusoids. By TEM, hepatocytes had angular shape with sinusoidal face and bile canalicular face. Hepatocytes had oval nucleus with peripheral heterochromatin and central electron lucent granules and a prominent nucleolus. Bile canaliculi were formed by two adjacent hepatocytes. Fenestrated endothelial cells with flat and elongated shape were found to be in the formation of hepatic sinusoidal wall. A narrow space of Disse was found between the sinusoidal endothelium and hepatocytes. Kupffer cells and pit cells were found within the sinusoidal lumen. Ito cells were found in the space of Disse. Research Highlights: By scanning electron microscopy, the liver parenchyma appeared as lobular with anastomosed one cell thick hepatic cell plates, which appeared as continuous sheets with small to large holes representing sinusoids. By transmission electron microscopy, hepatocytes had angular shape with sinusoidal face and bile canalicular face. Hepatocytes had oval nucleus with peripheral heterochromatin and central electron lucent granules and a prominent nucleolus. Abstract : Transmission electron micrograph of hepatocyte of 20‐week‐old guinea pig liver showing nucleus (N), mitochondria (M), golgi bodies (G), endoplasmic reticulum (ER) and junctional complex (J).